Super absorbent resin as well as preparation method and application thereof

Through step-by-step polymerization and surface crosslinking agent modification, the water absorption rate and liquid-through performance of the highly absorbent resin are improved, and the problems of complex processes and environmental pollution in the prior art are solved, and efficient and low-cost water absorption are achieved. Preparation of viable resin.

CN119192455AActive Publication Date: 2024-12-27SHANGHAI HUAYI NEW MATERIAL
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411031288.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-30
Publication Date
2024-12-27
Estimated Expiration
2044-07-30

AI Technical Summary

Technical Problem

The existing highly absorbent resins have shortcomings in water absorption rate and liquid-through performance, and the synthesis process is complex, the production cost is high, and the content of dissolved and residual monomers is high, resulting in environmental pollution.

Method used

By adopting a step-by-step polymerization method, first performing a first polymerization reaction in the aqueous phase to form a prepolymer, then performing a second polymerization reaction in a non-polar solvent to form an intermediate resin, and then modifying the surface crosslinking agent to obtain a water-absorbing resin. , by combining aqueous polymerization and reverse polymerization, the surface crosslinking agent is modified after the secondary particles are formed.

Benefits of technology

It significantly improves the water absorption rate and liquid permeability, simplifies the process flow, reduces production costs, reduces the content of dissolved and residual monomers, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192455A_ABST
    Figure CN119192455A_ABST
Patent Text Reader

Abstract

The invention provides super absorbent resin as well as a preparation method and application thereof, the preparation method comprises the following steps: step 1, performing a first polymerization reaction on a first polymeric monomer in an aqueous solution phase to obtain a prepolymer; 2, forming a dispersion liquid of the prepolymer in a non-polar solvent, adding a second polymerization monomer into the dispersion liquid, and carrying out a second polymerization reaction to prepare an intermediate resin; and step 3, modifying the intermediate resin by using a surface cross-linking agent to prepare the water-absorbent resin. The super absorbent resin with more excellent water absorption rate and high liquid permeability is synthesized through a simple and low-cost process design.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of polymers, and more specifically to a highly water-absorbent resin and a preparation method thereof, and also to products manufactured using the highly water-absorbent resin. Background Art

[0002] Super absorbent resin (SAP) is a polymer compound with strong water absorption and water retention capacity. It is widely used in the field of sanitary materials such as diapers and sanitary napkins, water-blocking materials for cables, sewage treatment materials, and water-retaining agents for agriculture, forestry, and gardening. With the high performance of diapers, which is its main use, people hope that absorbent resins have more and better functions, especially high water absorption rate, high water absorption speed, high water absorption rate under high pressure, high liquid permeability, low elution content, low residual monomer content, etc.

[0003] In order to meet the increasingly stringent requirements, relevant enterprises and research institutes are constantly developing newer SAP materials and their synthesis processes. For example, people have previously developed many different polymerization reaction processes for synthesis, and tried to make various adjustments to the reaction raw materials, additives, and process conditions in order to improve the various properties of the final SAP material. Unfortunately, the final results are always unsatisfactory. For example, the products obtained always inevitably have poor water absorption rate and liquid permeability (liquid permeability), and there are one or more of the following defects: too high content of dissolved matter, too high content of residual monomers, complex synthesis process, high production cost, long reaction time, more waste of catalysts and other raw materials, and environmental pollution caused by waste materials.

[0004] Therefore, the art is eager to develop a new technology for preparing SAP materials, which can have better water absorption rate and liquid permeability required by people in the art, and preferably can also solve one or more of the other defects mentioned above, and most preferably can solve all the defects mentioned above. Summary of the invention

[0005] In view of the above problems, the inventors of the present application conducted a lot of in-depth research and unexpectedly developed the method of the present invention, which effectively solves the difficult problems that have long been in urgent need of being solved in the prior art.

[0006] The first aspect of the present application provides a method for preparing a water-absorbent resin, the method comprising the following steps:

[0007] Step 1: allowing the first polymerizable monomer to undergo a first polymerization reaction in an aqueous solution phase to obtain a prepolymer;

[0008] Step 2: forming a dispersion of the prepolymer in a non-polar solvent, adding a second polymerizable monomer into the dispersion, and performing a second polymerization reaction to obtain an intermediate resin;

[0009] Step 3: modifying the intermediate resin with a surface cross-linking agent to obtain the water-absorbent resin; and

[0010] The first polymerized monomer and the second polymerized monomer are compounds containing at least one carbon-carbon double bond and at least one active group, respectively. The first polymerized monomer and the second polymerized monomer are the same or different.

[0011] According to one embodiment of the first aspect of the present application, before performing step three, no surface modification is performed using a surface cross-linking agent.

[0012] According to another embodiment of the first aspect of the present application, the surface cross-linking agent is polyol poly(glycidyl ether).

[0013] According to another embodiment of the first aspect of the present application, in step one and / or step two, one or more internal crosslinking agents are optionally used, and the internal crosslinking agent is selected from one or more of the following: poly(unsaturated carboxylic acid) polyol esters, polyacrylamides, poly(meth)acrylic acid carbamoyl esters, allylated starch, allylated cellulose, polycarboxylic acid poly(allyl esters), polyallyl isocyanurate, polyvinyl aromatic compounds, polyol poly(allyl) ethers.

[0014] According to another embodiment of the first aspect of the present application, the first polymerized monomer and the second polymerized monomer are the same as or different from each other, and are each independently selected from one or more of the following: (meth)acrylic acid, C1-C12 alkyl (meth)acrylate, C1-C12 hydroxyalkyl (meth)acrylate, (meth)acryloyl C2-C12 alkyl sulfonate, (meth)acrylamide C2-C12 alkyl sulfonic acid, hydroxyalkyl (meth)acryloyl phosphate, itaconic acid, cinnamic acid, vinyl sulfonic acid, allyl toluene sulfonic acid, vinyl toluene sulfonic acid, styrene sulfonic acid, (meth)acrylamide, N-ethyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylamide, mercapto-containing unsaturated monomers, phenolic hydroxyl-containing unsaturated monomers, and N-vinyl pyrrolidone.

[0015] According to another embodiment of the first aspect of the present application, the molar ratio of the first polymerized monomer to the second polymerized monomer is 1:10 to 10:1.

[0016] According to another embodiment of the first aspect of the present application, after step one and before step two, the prepolymer prepared in step one is crushed and sieved to obtain first primary particles of the prepolymer having a median particle size greater than or equal to 10 microns and less than 150 microns, which are used in step two.

[0017] According to another embodiment of the first aspect of the present application, in the step one and the step two, one or more selected from the following are optionally used: an initiator, a dispersion stabilizer, and an alkaline agent.

[0018] According to another embodiment of the first aspect of the present application, in the step 2, the non-polar solvent is selected from one or more of the following: n-hexane, n-heptane, cyclohexane, toluene and xylene.

[0019] According to another embodiment of the first aspect of the present application, an inorganic additive is added during, before or after one or more steps of steps one to three.

[0020] According to another embodiment of the first aspect of the present application, the water-absorbent resin is in the form of secondary particles formed by agglomeration of second primary particles, the median particle size of the secondary particles is 250-500 microns, and the median particle size of the second primary particles is 15-150 microns.

[0021] According to another embodiment of the first aspect of the present application, the step 1 is carried out at a temperature of 45-120° C., so that 60-100% of the first polymerizable monomers are polymerized.

[0022] According to another embodiment of the first aspect of the present application, step 2 is carried out at a temperature of 60-95°C.

[0023] According to another embodiment of the first aspect of the present application, the step three is carried out at a temperature of 50-100° C., and the amount of the surface crosslinking agent is 0.001-1% by weight, based on the total weight of the second polymerizable monomer as 100% by weight.

[0024] The second aspect of the present application provides a water-absorbent product, which includes: diapers, sanitary napkins, adult care pads, absorbent paper, napkins, disposable mattresses, soil moisturizing materials, leak-proof materials, sewage treatment materials, and mud solidification materials; at least a portion of the water-absorbent product contains the water-absorbent resin prepared by the method of the present invention.

[0025] In the specific implementation section below, the method, raw materials, process conditions and products of the present application are further introduced in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1A and Figure 1B The SEM image of the SAP particles prepared in the examples of the present application is shown. DETAILED DESCRIPTION

[0027] "Range" disclosed herein is in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundary of a particular range. All ranges that can be defined in this way include end values ​​and can be combined, i.e. any lower limit can be combined with any upper limit to form a range. For example, for a particular parameter, a range of 60-120 and 80-110 is listed, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.

[0028] In this application, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations.

[0029] In this application, unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.

[0030] In this application, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.

[0031] In this application, if there is no special explanation, the "including" mentioned herein means open or closed. For example, the "including" may mean that other components not listed may also be included, or only the listed components may be included.

[0032] According to a technical solution of the present application, the method of the present application includes the following steps: step 1: allowing a first polymerizable monomer to undergo a first polymerization reaction in an aqueous solution phase to obtain a prepolymer; step 2: forming a dispersion of the prepolymer in a non-polar solvent, adding a second polymerizable monomer to the dispersion, and conducting a second polymerization reaction to obtain an intermediate resin; step 3: modifying the intermediate resin with a surface cross-linking agent to obtain the water-absorbent resin.

[0033] One of the inventive points of the present invention is that, in a step-by-step manner, through a combination of aqueous phase polymerization and reverse phase polymerization, in the aqueous phase polymerization, the first polymerization monomer undergoes a first polymerization reaction to form first primary particles (particles). In the reverse phase polymerization, the newly added second polymerization monomer undergoes polymerization in the presence of the first primary particles to form second primary particles and the second primary particles are aggregated to form secondary particles. Figure 1A and 1B As shown, the SAP particles of the present application include secondary particles formed by agglomeration of primary particles (second primary particles).

[0034] Another aspect of the present invention is that the applicant unexpectedly discovered that after the reverse phase polymerization, that is, after the "secondary particles" have been formed, the surface modification using a surface crosslinking agent can achieve a significant increase in the product's water absorption rate and liquid permeability. However, there is a general technical prejudice in the prior art that the operation of surface modification using a surface crosslinking agent should be performed before the secondary particles are formed, rather than after the secondary particles are formed. If it is performed after the secondary particles are formed, it will not bring about significant performance improvements and may even have an adverse effect on water absorption. The present invention has achieved a completely unexpected technical effect after overcoming the above technical prejudice.

[0035] According to one embodiment of the present application, in the above step 1 and / or step 2, one or more internal cross-linking agents may be optionally used during the polymerization reaction.

[0036] In the present invention, the "internal crosslinking agent" refers to a crosslinking agent that exists within the polymerization reaction system during the process of polymerization to form the first primary particles (for the first step), the second primary particles and the secondary particles (for the second step), and crosslinks the polymer chains while forming them, thereby promoting the formation of the above-mentioned first primary particles and / or second primary particles and / or secondary particles.

[0037] The "surface crosslinking agent" is applied to the secondary particles after they have been formed. In the third step of "modification" using the surface crosslinking agent, the polymerization reaction related to the primary particles and / or secondary particles mentioned above does not occur.

[0038] According to one embodiment of the present application, the surface crosslinking agent is a polyol poly(glycidyl ether). Wherein polyol represents a C2-C16 polyol or a polymeric polyol containing two or more hydroxyls, for example, the polyol includes ethylene glycol, polyethylene glycol, propylene glycol, polypropylene glycol, polyethylene oxide glycol, polypropylene oxide glycol, butylene glycol, polybutylene glycol, glycerine, pentaerythritol, trimethylolpropane, etc. Two or more, for example two, three, four, five, six or all of the carboxyl groups in the polyol are connected to the corresponding number of glycidyl groups through ether bonds, thereby forming the polyol poly(glycidyl ether) of the present invention. According to an exemplary embodiment of the present application, the surface crosslinking agent includes one or more of the following: ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, polyethylene oxide glycol diglycidyl ether, polypropylene oxide glycol diglycidyl ether, butanediol diglycidyl ether, polybutylene glycol diglycidyl ether, glycerol triglycidyl ether, pentaerythritol tetraglycidyl ether, trimethylolpropane triglycidyl ether, etc. In the third step, the surface crosslinking agent can be directly applied to the slurry prepared in step 2, or the surface crosslinking agent and optional other components can be prepared into a solution, such as an aqueous solution, and then added to the slurry prepared in step 2.

[0039] According to one embodiment of the present application, based on the total molar amount of the first polymerized monomer and the second polymerized monomer as 100 mol%, the amount of the surface crosslinking agent can be 0.001-1 mol%, for example, it can be within the numerical range obtained by combining any two of the following numerical values: 0.001 mol%, 0.002 mol%, 0.005 mol%, 0.006 mol%, 0.008 mol%, 0.01 mol%, 0.02 mol%, 0.05 mol%, 0.06 mol%, 0.08 mol%, 0.1 mol%, 0.3 mol%, 0.5 mol%, 0.6 mol%, 0.8 mol%, 0.9 mol%, 1 mol%.

[0040] According to one embodiment of the present application, the internal crosslinking agent is used in step one, or in step two, or in both step one and step two. The internal crosslinking agent is selected from one or more of the following: poly(unsaturated carboxylic acid) polyol esters, polyacrylamides, poly(meth)acrylic acid carbamoyl esters, allylated starch, allylated cellulose, polycarboxylic acid poly(allyl esters), polyallyl isocyanurate, polyvinyl aromatic compounds, polyol poly(allyl) ethers. Wherein the polyol represents a C2-C16 polyol or polymeric polyol containing two or more hydroxyl groups, for example, the polyol includes ethylene glycol, polyethylene glycol, propylene glycol, polypropylene glycol, polyethylene oxide glycol, polypropylene oxide glycol, butylene glycol, polybutylene glycol, glycerol, pentaerythritol, trimethylolpropane, etc. For example, the internal crosslinking agent can be selected from one or more of the following: poly[(meth)acrylic acid] polyol esters, poly(maleic acid) polyol esters, poly(fumaric acid) polyol esters; di(meth)acrylic acid aminoformyl esters obtained by reacting polyisocyanates such as toluene diisocyanate or hexamethylene diisocyanate with hydroxyethyl (meth)acrylate; allylated starch; allylated cellulose; diallyl phthalate; N,N',N"-triallyl isocyanurate; divinylbenzene; pentaerythritol triallyl ether; polyethyleneimine, etc. Preferably, the internal crosslinking agent is selected from one or more of the following: N,N'-methylenebisacrylamide, polyethylene glycol diacrylate, pentaerythritol triallyl ether.

[0041] According to one embodiment of the present application, when an internal crosslinking agent is used in step one, based on the total molar amount of the first polymerized monomer as 100 mol%, the amount of the internal crosslinking agent used in the first step can be 0.002-1 mol%. For example, it can be within the numerical range obtained by combining any two of the following numerical values: 0.002 mol%, 0.005 mol%, 0.006 mol%, 0.008 mol%, 0.01 mol%, 0.02 mol%, 0.05 mol%, 0.06 mol%, 0.08 mol%, 0.1 mol%, 0.3 mol%, 0.5 mol%, 0.6 mol%, 0.8 mol%, 0.9 mol%, 1 mol%.

[0042] According to another embodiment of the present application, when an internal crosslinking agent is used in step 2, based on the total molar amount of the second polymerizable monomer as 100 mol%, the amount of the internal crosslinking agent used in the second step can be 0.002-1 mol%, for example, the value obtained by combining any two of the following values:

[0043] Within the range: 0.002 mol%, 0.005 mol%, 0.006 mol%, 0.008 mol%, 0.01 mol%, 0.02 mol%, 0.05 mol%, 0.06 mol%, 0.08 mol%, 0.1 mol%, 0.3 mol%, 0.5 mol%, 0.6 mol%, 0.8 mol%, 0.9 mol%, 1 mol%.

[0044] According to one embodiment of the present application, the first polymerizable monomer used in step one and the second polymerizable monomer used in step two may be the same or different from each other, and each contains at least one carbon-carbon double bond and at least one active group, and the active group may be a carboxyl group, a hydroxyl group, an amino group, an amide group, a sulfonic acid group, a thiol group, etc. For example, the first polymerized monomer and the second polymerized monomer can be independently selected from one or more of the following: (meth)acrylic acid, C1-C12 alkyl (meth)acrylate, C1-C12 hydroxyalkyl (meth)acrylate, (meth)acryloyl C2-C12 alkyl sulfonate, (meth)acrylamide C2-C12 alkyl sulfonic acid, hydroxyalkyl (meth)acryloyl phosphate, itaconic acid, cinnamic acid, vinyl sulfonic acid, allyl toluene sulfonic acid, vinyl toluene sulfonic acid, styrene sulfonic acid, (meth)acrylamide, N-ethyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylamide, mercapto-containing unsaturated monomers, phenolic hydroxyl-containing unsaturated monomers, and N-vinyl pyrrolidone. According to an exemplary embodiment, the first polymerizable monomer and the second polymerizable monomer are each independently selected from one or more of the following: (meth)acrylic acid, maleic acid (anhydride), itaconic acid, cinnamic acid, vinyl sulfonic acid, allyl toluene sulfonic acid, vinyl toluene sulfonic acid, styrene sulfonic acid, 2-(meth)acrylamide-2-methylpropane sulfonic acid, 2-(meth)acryloylethane sulfonic acid, 2-(meth)acryloylpropane sulfonic acid, 2-hydroxyethyl (meth)acryloyl phosphate and other acid group-containing unsaturated monomers; (meth)acrylamide, N-ethyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide and other amide group-containing unsaturated monomers; N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylamide and other amino group-containing unsaturated monomers; mercapto group-containing unsaturated monomers; phenolic hydroxyl-containing unsaturated monomers; N-vinyl pyrrolidone and other lactam group-containing unsaturated monomers.

[0045] According to one embodiment of the present application, the weight ratio of the first polymerized monomer to the second polymerized monomer can be 1:10 to 10:1, for example, it can be within the numerical range obtained by combining any two of the following ratios: 1:10, 1:9, 1:8, 1:7, 1:6, 1:5, 1:4, 1:3, 1:2, 1:1, 3:2, 4:3, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1.

[0046] According to a specific embodiment of the present application, in the step 1, a first monomer aqueous solution containing a first polymerizable monomer and a first initiation system is prepared, and the aqueous solution of the first polymerizable monomer is subjected to aqueous solution polymerization reaction to obtain a primary polymer.

[0047] According to one embodiment of the present application, the step one is carried out at a temperature of 45-120°C. For example, the reaction temperature of the step one can be within the numerical range obtained by combining any two of the following numerical values: 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C.

[0048] According to another embodiment of the present application, in step one, 60-100% of the first polymerized monomers are polymerized, for example, 70-100% of the first polymerized monomers are polymerized, or 80-100% of the first polymerized monomers are polymerized, or 90-100% of the first polymerized monomers are polymerized.

[0049] According to one embodiment of the present application, after the prepolymer is prepared, it is dried, crushed and classified to obtain first primary particles, which are then used in step 2. The first primary particles may be irregularly shaped particles with edges and corners.

[0050] According to one embodiment of the present application, the median particle size of the first primary particles is greater than or equal to 10 microns and less than 150 microns. For example, the median particle size of the first primary particles can be within the numerical range obtained by combining any two of the following values: 15 microns, 20 microns, 30 microns, 40 microns, 45 microns, 50 microns, 60 microns, 70 microns, 80 microns, 90 microns, 100 microns, 110 microns, 120 microns, 130 microns, 140 microns, and 145 microns.

[0051] According to one embodiment of the present application, in step 2, the first primary particles of the above-mentioned primary polymer are dispersed in a non-polar solvent containing a dispersion stabilizer, and a second monomer aqueous solution containing a second polymerization monomer and a second initiation system is prepared, and then the second monomer aqueous solution is added to the non-polar solvent of the first primary particles, and an intermediate resin is obtained through a reverse suspension polymerization reaction. The intermediate resin contains secondary particles formed by the aggregation and stacking of the second primary particles.

[0052] Then in step three, the intermediate resin secondary particles are modified using a surface crosslinking agent to obtain the SAP particles of the present invention. The temperature of step three can be 50-100°C, such as 60-90°C, or 75-85°C.

[0053] According to one embodiment of the present application, inorganic additives such as silica, talc, zeolite, alumina powder, etc. may be added after step 2 or step 3. The content of the inorganic additives may be 0.01-5 parts by mass based on 100 parts by mass of SAP.

[0054] According to one embodiment of the present application, the median particle size of the secondary particles obtained by the method is 250-500 microns, preferably 300-450 microns, and more preferably 350-420 microns.

[0055] According to one embodiment of the present application, when the first monomer and the second monomer used in step 1 and step 2 have acidic groups such as carboxyl groups and sulfonic acid groups, it may be necessary to add an alkaline agent (neutralizer) to the polymerization reaction system, for example, an alkali metal hydroxide or ammonium hydroxide, such as sodium hydroxide, potassium hydroxide, lithium hydroxide, ammonium hydroxide, etc., or a mixture of two or more of the above bases. According to one embodiment of the present application, the amount of the alkaline agent added should neutralize the acidic groups in all monomers by 10-100 mol%, such as 20-90 mol%, or 30-80 mol%.

[0056] In the step 1 and the step 2, an initiator may be added, for example, a free radical initiator, examples of which may include persulfates (potassium persulfate, ammonium persulfate, sodium persulfate, etc.), peroxides (methyl ethyl ketone peroxide, methyl isobutyl ketone peroxide, di-tert-butyl peroxide, tert-butyl isopropyl peroxide, tert-butyl peroxyacetate, tert-butyl peroxyisobutyrate, tert-butyl peroxypivalate, hydrogen peroxide, etc.), and azo compounds (2,2'-azobis[2-(N-phenylamidino)propane]·dihydrochloride, 2,2'-azobis[2-(N-allylamidino)propane]·dihydrochloride, 2,2'-azobis{2-[1-(2-hydroxyethyl)-2-imidazolin-2-yl]propane}·dihydrochloride , 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide}, 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)-propionamide] and 4,4'-azobis(4-cyanovaleric acid). The free radical polymerization initiator can be used alone or as a mixture of two or more. Preferably, the free radical polymerization initiator is selected from one or more of potassium persulfate, ammonium persulfate, and sodium persulfate. The first initiator used in the step one and the second initiator used in the step two can be the same or different. The above-mentioned free radical polymerization initiator can be combined with sodium sulfite, sodium bisulfite, ferrous sulfate and / or L-ascorbic acid as a redox polymerization initiator.

[0057] In the first step, based on the total molar amount of the first polymerized monomer as 100 mol%, the amount of the first initiator can be 0.005-1 mol%, for example, it can be within the numerical range obtained by combining any two of the following values: 0.008 mol%, 0.01 mol%, 0.03 mol%, 0.05 mol%, 0.08 mol%, 0.1 mol%, 0.2 mol%, 0.3 mol%, 0.5 mol%, 0.8 mol%, 0.9 mol%, 1 mol%.

[0058] In the second step, based on the total molar amount of the second polymerizable monomer as 100 mol%, the amount of the second initiator used can be 0.005-1 mol%, for example, it can be within the numerical range obtained by combining any two of the following values: 0.008 mol%, 0.01 mol%, 0.03 mol%, 0.05 mol%, 0.08 mol%, 0.1 mol%, 0.2 mol%, 0.3 mol%, 0.5 mol%, 0.8 mol%, 0.9 mol%, 1 mol%.

[0059] According to one embodiment of the present application, a dispersion stabilizer can be used in the first step and / or the second step. The dispersion stabilizer may include a surfactant, preferably a nonionic surfactant. The surfactant may be one or more selected from the group consisting of sucrose fatty acid esters, polyglycerol fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene glycerol fatty acid esters, sorbitol fatty acid esters, polyoxyethylene sorbitol fatty acid esters, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene castor oils, polyoxyethylene hardened castor oils, alkyl allyl formaldehyde-polyoxyethylene ether condensates, polyoxyethylene polyoxypropylene block copolymers, polyoxyethylene polyoxypropyl alkyl ethers, polyethylene glycol fatty acid esters, alkyl glucosides, N-alkyl glucamides, polyoxyethylene fatty amides, polyoxyethylene alkylamines, phosphates of polyoxyethylene alkyl ethers, and phosphates of polyoxyethylene alkyl allyl ethers. The surfactant as a dispersion stabilizer may be used alone or in combination with more than two kinds. Among them, one or more of sucrose fatty acid esters, polyglycerol fatty acid esters, sorbitan fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene glycerol fatty acid esters, and polyoxyethylene hydrogenated castor oil are preferred from the viewpoint of dispersion stability of the aqueous monomer solution.

[0060] The dispersion stabilizer can also include a polymer dispersant, or the polymer dispersant can be used simultaneously with the above-mentioned surfactant. The polymer dispersant used can be the following types: maleic anhydride modified polyethylene, maleic anhydride modified polypropylene, maleic anhydride modified ethylene-propylene copolymer, maleic anhydride modified EPDM (ethylene-propylene-diene terpolymer), maleic anhydride modified polybutadiene, ethylene-maleic anhydride copolymer, ethylene-propylene-maleic anhydride copolymer, butadiene-maleic anhydride copolymer, oxidized polyethylene, ethylene-acrylic acid copolymer, ethyl cellulose, ethyl hydroxyethyl cellulose, etc. The polymer dispersant can be used alone or in combination of two or more. The polymer dispersant preferably includes one or more of maleic anhydride modified polyethylene, maleic anhydride modified polypropylene, maleic anhydride modified ethylene-propylene copolymer, oxidized polyethylene, oxidized polypropylene and ethylene-acrylic acid copolymer.

[0061] According to one embodiment of the present application, for the first step, if a dispersion stabilizer is used, the total weight of the first polymerized monomer is 100 parts by weight, and the amount of the dispersion stabilizer is 0.01-6 parts by weight.

[0062] According to one embodiment of the present application, for the second step, if a dispersion stabilizer is used, the total weight of the second polymerizable monomer is 100 parts by weight, and the amount of the dispersion stabilizer is 0.1-5 parts by weight, preferably 0.5-2 parts by weight.

[0063] According to one embodiment of the present application, the non-polar solvent used in step 2 is also called a hydrophobic solvent, and the solvent is preferably a petroleum hydrocarbon solvent, more preferably one or more selected from the following: n-hexane, n-heptane, cyclohexane, toluene and xylene.

[0064] According to another embodiment of the present application, the step 2 is carried out at a temperature of 60-95°C. For example, the reaction temperature of the step 2 can be within the numerical range obtained by combining any two of the following numerical values: 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C.

[0065] In the following examples, the excellent effects that can be achieved by the method of the present application are specifically described. The purpose is to better understand the content of the present application. It should be understood that these examples are merely illustrative and not restrictive. The reagents used in the examples are conventionally purchased from the market unless otherwise specified. The methods and conditions used in the examples are conventional methods and conditions unless otherwise specified.

[0066] Example

[0067] All raw materials used in the following examples were commercially available analytically pure raw materials and were used directly without further treatment.

[0068] In the following examples, median particle size measurement and control and performance testing of water-absorbent resin products were performed by the following techniques:

[0069] A. Median particle size (micrometers)

[0070] The test method for the median particle size of the primary particles obtained in step 1 is as follows:

[0071] All the primary particles after the pulverization were collected and sieved through JIS standard sieves (meshing openings of 425 μm, 250 μm, 180 μm, 150 μm, 106 μm, 75 μm, and 45 μm).

[0072] JIS standard sieves with mesh sizes of 425 μm, 250 μm, 180 μm, 150 μm, 106 μm, 75 μm, and 45 μm were stacked in descending order, and the water-absorbent resin particles were added to the top sieve. The sieve was vibrated for 10 minutes using a rotary tapping vibrating sieve.

[0073] Then, the mass percentage of the water-absorbent resin particles remaining on each sieve relative to the total amount is calculated, and the relationship between the mesh size of the sieve and the integrated value of the mass percentage of the water-absorbent resin particles remaining on the sieve is plotted on a logarithmic probability paper. Each point on the probability paper is connected by a straight line, and the median particle size of the secondary particles is defined as the particle size corresponding to the cumulative mass percentage of 50% by mass.

[0074] The test method for the median particle size of the secondary particles obtained in stage 2 is as follows:

[0075] All the secondary particles after drying were collected and sieved through JIS standard sieves (mesh openings of 850 μm, 710 μm, 600 μm, 500 μm, 425 μm, 300 μm, 180 μm, and 150 μm).

[0076] JIS standard sieves with mesh sizes of 850 μm, 710 μm, 600 μm, 500 μm, 425 μm, 300 μm, 180 μm, and 150 μm were stacked in descending order, and the water-absorbent resin particles were added to the top sieve, and the sieve was vibrated for 10 minutes using a rotary tapping vibration sieve.

[0077] Then, the mass percentage of the water-absorbent resin particles remaining on each sieve relative to the total amount is calculated, and the relationship between the mesh size of the sieve and the integrated value of the mass percentage of the water-absorbent resin particles remaining on the sieve is plotted on a logarithmic probability paper. Each point on the probability paper is connected by a straight line, and the median particle size of the secondary particles is defined as the particle size corresponding to the cumulative mass percentage of 50% by mass.

[0078] B. Water absorption rate of SAP products (seconds)

[0079] Add 0.02 parts by weight of indigo as a food additive to 1000 parts by weight of a 0.90 wt% NaCl aqueous solution prepared in advance, and adjust the liquid temperature to 25°C. Add 50 g of a 0.90 wt% NaCl aqueous solution colored blue to a 100 ml beaker, and while stirring at 600 rpm with a cylindrical stirring blade of 20 mm in length and 5 mm in thickness, add 2.0 g of a highly absorbent resin. Start timing the moment the addition is completed, and the end point is when the low point of the liquid vortex just covers the stirring blade. This time interval t is the water absorption rate. The smaller t is, the faster the salt water absorption rate is.

[0080] C. Liquid permeability (seconds)

[0081] Weigh 150g of 0.9wt% NaCl solution adjusted to 23°C, add 0.32g of the highly absorbent resin test sample accurately weighed, and let it stand for swelling for 30min. Fix the infiltration tube vertically, with a filter screen and a plug at the lower end, and mark the capacity scale interval. The inner diameter of the infiltration tube is 30mm, and the length of the capacity scale interval is 35mm. The time required for the 23°C 0.9wt% NaCl solution to flow through the scale interval of the infiltration tube is tested and recorded as T1. Transfer the prepared hydrogel particles and saline to the infiltration tube together. When the swollen gel particles sink to the lower end, place a pressure shaft with a circular metal wire mesh with sieve holes on it, and place a weight on the top of the pressure shaft. Then open the valve at the bottom of the infiltration tube, and record the time T2 for the saline to flow through its scale interval. The total pressure applied to the swollen gel particles by the pressure shaft and the weight is 2.0kPa. The less time it takes for liquid to pass through the permeation tube, the better the liquid permeability of the superabsorbent resin, and its value is calculated as follows: T2-T1.

[0082] D. Pure water absorption in 1 minute (g / g)

[0083] Weigh 2.0000±0.001g of sample into a 400-mesh nylon mesh bag and record the weight W1. Fill a 5L beaker with 2 / 3 of pure water and control the temperature at 23±0.5℃. Quickly immerse the nylon mesh bag containing the sample in pure water and start timing. After 1 minute, take the nylon mesh bag out of the pure water and leave it for a few seconds until there is no water dripping from the bottom. After weighing and resetting the nylon mesh bag after absorbing water, clean up all the SAP particles in the bag after absorbing water, then put the empty bag on the balance and weigh it, and record the weight W2. Calculate CRC according to the following formula.

[0084] Pure water absorption in 1 minute = (W2-W1) / W1

[0085] E. Centrifugal water retention capacity (g / g)

[0086] The centrifuge retention capacity (CRC) of superabsorbent resin is measured according to the EDANA method (ERT441.2-02). "ENANA" is the abbreviation of the European Association of the Nonwovens Industry. "ERT" is the abbreviation of the European standard method for measuring superabsorbent resin. In the present invention, unless otherwise specified, the physical properties of superabsorbent resin are measured in accordance with the original ERT (revised version in 2002 / known literature).

[0087] Specifically, 0.20 g of the superabsorbent resin was uniformly placed in a tea bag (60 mm × 85 mm) and heat-sealed, and then immersed in a far excess (usually about 500 ml) of a 0.90 wt% NaCl aqueous solution at 23 (±2)°C. After 30 minutes, the bag was lifted up and water was removed at a centrifugal force of 250 G for 3 minutes using a centrifugal separator (manufactured by Kokusan Co., Ltd., model H-122), and the weight of the bag was measured. In addition, the same operation was performed without using the superabsorbent resin, and the weight at this time was measured. W2g, and CRC was calculated according to the following formula.

[0088] CRC = (W1-W2) / 0.2-1

[0089] Example 1

[0090] (a) Aqueous phase polymerization step: In a PP beaker with a volume of 2000 ml, 174.78 g of acrylic acid (purchased from Shanghai Huayi New Materials Co., Ltd.), 148.19 g of deionized water and 69.84 g of a 50 wt% NaOH aqueous solution (purchased from Shanghai Chlor-Alkali Chemical Co., Ltd.) were added, wherein the NaOH solution needed to be added under strong stirring. During the addition of the NaOH solution, precipitates could be observed, but gradually dissolved to form a transparent uniform solution, and the temperature of the material rose to 65°C. The material was cooled to 56°C, and then 23.59 g of polyethylene glycol diacrylate 400 (purchased from Taiwan Changxing Materials Co., Ltd., as a 4% aqueous solution) was added as an internal crosslinking agent. Then 71.79 g of a 50 wt% NaOH aqueous solution at 40°C was added. After the addition was completed, the material temperature rose to 88°C due to the neutralization heat. The temperature of the reaction liquid was lowered to 78°C, and 11.32 g of a 3% sodium persulfate aqueous solution was added thereto to obtain the monomer aqueous solution of step one, which was stirred for 2 seconds. Then, while stirring, it was quickly poured into a 25*25 cm stainless steel tray preheated to 105°C, and the entire tray was placed in an oven at 105°C. After 20 to 30 seconds, the polymerization reaction began. During the polymerization reaction, water vapor was generated while expanding and bubbling in all directions, and then it shrank and collapsed into a size slightly larger than the polymerization disk. After 3 minutes from the start of the polymerization reaction, the cross-linked polymer containing a ribbon-like hydrogel was taken out from the polymerization disk. The peak temperature during polymerization was 110°C.

[0091] The hydrogel obtained by the aqueous phase polymerization reaction was broken up using a meat grinder (purchased from Zhengyuan Precision Machinery Co., Ltd., model RY-12S, pore size 8 mm) to obtain a granular hydrogel. During the gel breaking process, about 90 g of deionized water at a temperature of 90° C. was continuously and evenly sprayed onto the gel.

[0092] The granular hydrogel obtained by the above operation was spread on a stainless steel wire mesh with a mesh size of 850 μm and dried in a blast oven at 185° C. for 70 min. Next, the dried polymer obtained by the drying operation was crushed using a grinder and sieved and classified using standard sieves with mesh sizes of 45 μm and 150 μm to obtain primary particles with a particle size of 45 μm to 150 μm.

[0093] (b) Reverse suspension polymerization step: 124.4 g of acrylic acid was added to a 500 ml conical flask, and 189.9 g of a 27% by mass aqueous sodium hydroxide solution was added dropwise in an ice-water bath to neutralize 74% by mole of the acrylic acid. Then, 0.192 g of potassium persulfate and 13.9 mg of N,N'-methylenebisacrylamide (No.: 14085E, purchased from Adamas Reagent Co., Ltd.) were added and dissolved, and 20 g of water was added to prepare the monomer aqueous solution of step 2.

[0094] Prepare a 1000mL five-mouth detachable flask, install a reflux condenser, a nitrogen inlet tube, and a stirring paddle (crescent paddle with a blade diameter of 80mm) as a stirrer on the flask. Place the entire flask in an oil bath and heat it to 80°C. Add 408ml of n-heptane, 1.104g of sucrose stearate (Mitsubishi Chemical Corporation, Ryoto sucrose ester S-370), and 1.104g of maleic anhydride-modified ethylene-propylene copolymer (Mitsui Chemicals, Inc., Hi-wax1105A) to the flask to dissolve the dispersion stabilizer. Adjust the rotation speed to 500rpm, weigh 110g of the primary particles obtained by the above-mentioned aqueous phase polymerization and add them to the flask, and add 100g of water thereto.

[0095] The water bath temperature was lowered to 20°C, and the aqueous monomer solution of the second stage described above was added into the flask. After the addition was completed, the air in the system was replaced with nitrogen for 30 minutes, and then the flask was immersed in a 70°C water bath for 60 minutes to obtain the slurry of step 2 through polymerization.

[0096] (c) Surface modification step: The slurry obtained in the above step was placed in an oil bath at 120°C to make water and n-heptane azeotropic. While ensuring the reflux of n-heptane, 230 g of water was removed from the system, and then the oil bath temperature was cooled to 80°C. 10.34 g of a 2% aqueous solution of ethylene glycol diglycidyl ether (No. 38399B, purchased from Adamas Reagent Co., Ltd.) was added and kept at 80°C for 120 min. The n-heptane was evaporated and dried. 260.1 g of secondary particles were obtained by the method. The median particle size of the secondary particles was 402.4 μm, and the particle size distribution results are shown in Table 1. 100 parts by weight of the absorbent resin was mixed with 0.3 parts by weight of AEROSIL 200 (gas phase SiO2, Degussa) to obtain a final resin sample. The results of the performance measurements are shown in Table 2. Figure 1A and Figure 1B The microscopic morphology of the product at different magnifications is shown respectively, and it can be seen that the product includes secondary particles formed by the aggregation of a large number of irregularly shaped primary particles.

[0097] Example 2

[0098] (a) Aqueous phase polymerization step: In a PP beaker with a volume of 2000 ml, 174.78 g of acrylic acid (purchased from Shanghai Huayi New Materials Co., Ltd.), 148.19 g of deionized water and 69.84 g of a 50 wt% NaOH aqueous solution (purchased from Shanghai Chlor-Alkali Chemical Co., Ltd.) were added, wherein the NaOH solution needed to be added under strong stirring. During the addition of the NaOH solution, precipitates could be observed, but gradually dissolved to form a transparent uniform solution, and the temperature of the material rose to 65°C. The material was cooled to 56°C, and then 23.59 g of polyethylene glycol diacrylate 400 (purchased from Taiwan Changxing Materials Co., Ltd., as a 4% aqueous solution) was added as an internal crosslinking agent. Then 71.79 g of a 50 wt% NaOH aqueous solution at 40°C was added. After the addition was completed, the material temperature rose to 88°C due to the neutralization heat. The temperature of the reaction liquid was lowered to 78°C, and 11.32 g of a 3% sodium persulfate aqueous solution was added thereto to obtain the monomer aqueous solution of step one, which was stirred for 2 seconds. Then, while stirring, it was quickly poured into a 25*25 cm stainless steel tray preheated to 105°C, and the entire tray was placed in an oven at 105°C. After 20 to 30 seconds, the polymerization reaction began. During the polymerization reaction, water vapor was generated while expanding and bubbling in all directions, and then it shrank and collapsed into a size slightly larger than the polymerization disk. After 3 minutes from the start of the polymerization reaction, the cross-linked polymer containing a ribbon-like hydrogel was taken out from the polymerization disk. The peak temperature during polymerization was 110°C.

[0099] The hydrogel obtained by the aqueous phase polymerization reaction was broken up using a meat grinder (purchased from Zhengyuan Precision Machinery Co., Ltd., model RY-12S, pore size 8 mm) to obtain a granular hydrogel. During the gel breaking process, about 90 g of deionized water at a temperature of 90° C. was continuously and evenly sprayed onto the gel.

[0100] The granular hydrogel obtained by the above operation was spread on a stainless steel wire mesh with a mesh size of 850 μm and dried in a blast oven at 185° C. for 70 min. Next, the dried polymer obtained by the drying operation was crushed using a grinder and sieved and classified using standard sieves with mesh sizes of 45 μm and 150 μm to obtain primary particles with a particle size of 45 μm to 150 μm.

[0101] (b) Reverse suspension polymerization step: 124.4 g of acrylic acid was added to a 500 ml conical flask, and 189.9 g of a 27% by mass aqueous sodium hydroxide solution was added dropwise in an ice-water bath to neutralize 74% by mole of the acrylic acid. Then, 0.192 g of potassium persulfate and 13.9 mg of N,N'-methylenebisacrylamide (No.: 14085E, purchased from Adamas Reagent Co., Ltd.) were added and dissolved, and 20 g of water was added to prepare the monomer aqueous solution of step 2.

[0102] Prepare a 1000mL five-mouth detachable flask, install a reflux condenser, a nitrogen inlet tube, and a stirring paddle (crescent paddle with a blade diameter of 80mm) as a stirrer on the flask. Place the entire flask in an oil bath and heat it to 80°C, add 408ml of n-heptane, 1.104g of sucrose stearate (Mitsubishi Chemical Corporation, Ryoto sucrose ester S-370), and 1.104g of maleic anhydride modified ethylene-propylene copolymer (Mitsui Chemicals, Inc., Hi-wax1105A) to the flask to dissolve the dispersion stabilizer. Adjust the rotation speed to 500rpm, weigh 110g of the primary particles obtained by the above-mentioned aqueous phase polymerization and add them to the flask, and add 80g of water thereto.

[0103] The water bath temperature was lowered to 20°C, and the aqueous monomer solution of the second stage described above was added into the flask. After the addition was completed, the air in the system was replaced with nitrogen for 30 minutes, and then the flask was immersed in a 70°C water bath for 60 minutes to obtain the slurry of step 2 through polymerization.

[0104] (c) Surface modification step: The slurry obtained in the above step was placed in an oil bath at 120°C to make water and n-heptane azeotropic. While ensuring the reflux of n-heptane, 230 g of water was removed from the system, and then the oil bath temperature was cooled to 80°C. 10.34 g of a 2% aqueous solution of ethylene glycol diglycidyl ether (No. 38399B, purchased from Adamas Reagent Co., Ltd.) was added and kept at 80°C for 120 min. The n-heptane was evaporated and dried. 259.4 g of secondary particles were obtained by the method. The median particle size of the secondary particles was 365.0 μm, and the particle size distribution results are shown in Table 1. 100 parts by weight of the absorbent resin was mixed with 0.3 parts by weight of AEROSIL 200 (gas phase SiO2, Degussa) to obtain a final resin sample. The results of the measurement of various properties are shown in Table 2. Its SEM image shows that the product includes secondary particles formed by agglomeration of a large number of irregularly shaped primary particles.

[0105] Example 3

[0106] (a) Aqueous phase polymerization step: In a PP beaker with a volume of 2000 ml, 174.78 g of acrylic acid (purchased from Shanghai Huayi New Materials Co., Ltd.), 148.19 g of deionized water and 69.84 g of a 50 wt% NaOH aqueous solution (purchased from Shanghai Chlor-Alkali Chemical Co., Ltd.) were added, wherein the NaOH solution needed to be added under strong stirring. During the addition of the NaOH solution, precipitates could be observed, but gradually dissolved to form a transparent uniform solution, and the temperature of the material rose to 65°C. The material was cooled to 56°C, and then 23.59 g of polyethylene glycol diacrylate 400 (purchased from Taiwan Changxing Materials Co., Ltd., as a 4% aqueous solution) was added as an internal crosslinking agent. Then 71.79 g of a 50 wt% NaOH aqueous solution at 40°C was added. After the addition was completed, the material temperature rose to 88°C due to the neutralization heat. The temperature of the reaction liquid was lowered to 78°C, and 11.32 g of a 3% sodium persulfate aqueous solution was added thereto to obtain the monomer aqueous solution of step one, which was stirred for 2 seconds. Then, while stirring, it was quickly poured into a 25*25 cm stainless steel tray preheated to 105°C, and the entire tray was placed in an oven at 105°C. After 20 to 30 seconds, the polymerization reaction began. During the polymerization reaction, water vapor was generated while expanding and bubbling in all directions, and then it shrank and collapsed into a size slightly larger than the polymerization disk. After 3 minutes from the start of the polymerization reaction, the cross-linked polymer containing a ribbon-like hydrogel was taken out from the polymerization disk. The peak temperature during polymerization was 110°C.

[0107] The hydrogel obtained by the aqueous phase polymerization reaction was broken up using a meat grinder (purchased from Zhengyuan Precision Machinery Co., Ltd., model RY-12S, pore size 8 mm) to obtain a granular hydrogel. During the gel breaking process, about 90 g of deionized water at a temperature of 90° C. was continuously and evenly sprayed onto the gel.

[0108] The granular hydrogel obtained by the above operation was spread on a stainless steel wire mesh with a mesh size of 850 μm and dried in a blast oven at 185° C. for 70 min. Next, the dried polymer obtained by the drying operation was crushed using a grinder and sieved and classified using standard sieves with mesh sizes of 45 μm and 150 μm to obtain primary particles with a particle size of 45 μm to 150 μm.

[0109] (b) Reverse suspension polymerization step: 124.4 g of acrylic acid was added to a 500 ml conical flask, and 189.9 g of a 27% by mass aqueous sodium hydroxide solution was added dropwise in an ice-water bath to neutralize 74% by mole of the acrylic acid. Then, 0.192 g of potassium persulfate and 13.9 mg of N,N'-methylenebisacrylamide (No.: 14085E, purchased from Adamas Reagent Co., Ltd.) were added and dissolved, and 20 g of water was added to prepare the monomer aqueous solution of step 2.

[0110] Prepare a 1000mL five-mouth detachable flask, install a reflux condenser, a nitrogen inlet tube, and a stirring paddle (crescent paddle with a blade diameter of 80mm) as a stirrer on the flask. Place the entire flask in an oil bath and heat it to 80°C, add 408ml of n-heptane, 1.104g of sucrose stearate (Mitsubishi Chemical Corporation, Ryoto sucrose ester S-370), and 1.104g of maleic anhydride modified ethylene-propylene copolymer (Mitsui Chemicals, Inc., Hi-wax1105A) to the flask to dissolve the dispersion stabilizer. Adjust the rotation speed to 500rpm, weigh 110g of the primary particles obtained by the above-mentioned aqueous phase polymerization and add them to the flask, and add 120g of water thereto.

[0111] The water bath temperature was lowered to 20°C, and the aqueous monomer solution of the second stage described above was added into the flask. After the addition was completed, the air in the system was replaced with nitrogen for 30 minutes, and then the flask was immersed in a 70°C water bath for 60 minutes to obtain the slurry of step 2 through polymerization.

[0112] (c) Surface modification step: The slurry obtained in the above step was placed in an oil bath at 120°C to make water and n-heptane azeotropic. While ensuring the reflux of n-heptane, 230 g of water was removed from the system, and then the oil bath temperature was cooled to 80°C. 10.34 g of a 2% aqueous solution of ethylene glycol diglycidyl ether (No. 38399B, purchased from Adamas Reagent Co., Ltd.) was added and kept at 80°C for 120 min. The n-heptane was evaporated and dried. 266.9 g of secondary particles were obtained by the method. The median particle size of the secondary particles was 390.7 μm, and the particle size distribution results are shown in Table 1. 100 parts by weight of the absorbent resin was mixed with 0.3 parts by weight of AEROSIL 200 (gas phase SiO2, Degussa) to obtain a final resin sample. The results of the performance measurements are shown in Table 2. Its SEM image shows that the product includes secondary particles formed by agglomeration of a large number of irregularly shaped primary particles.

[0114] Example 4

[0115] (a) Aqueous phase polymerization step: A polymerization reaction is carried out in a belt reactor. 154.8 g of acrylic acid (purchased from Shanghai Huayi New Materials Co., Ltd.), 0.62 g of a cross-linking agent pentaerythritol triallyl ether (No.: 01140358, purchased from Adamas Reagent Co., Ltd.) and 343 g of deionized water are added, stirred and mixed, and the temperature is maintained at 3°C. Nitrogen is flowed into the mixture to make the dissolved oxygen content in the mixture less than 1 ppm, and then 0.6 g of a 1% hydrogen peroxide aqueous solution, 1 g of a 2% ascorbic acid aqueous solution and 2.3 g of a 2% 2,2-azobis[2-(imidazoline-2-yl)propane] dihydrochloride aqueous solution are added thereto while maintaining mixing to start the polymerization reaction. After the temperature of the mixture reaches 90°C, the mixture is polymerized at a temperature of 90±2°C for about 5 hours to obtain a water-containing gel.

[0116] After the polymerization reaction was completed, the hydrogel was ground with a meat grinder (Zhengyuan Precision Machinery Co., Ltd., model RY-12S, pore size 8 mm), and 108 g of 48.5% sodium hydroxide aqueous solution was added for neutralization to obtain a neutralized gel.

[0117] The granular hydrogel obtained by the above operation was spread on a stainless steel wire mesh with a mesh size of 850 μm and dried in a blast oven at 185° C. for 70 min. Next, the dried polymer obtained by the drying operation was crushed using a grinder and sieved and classified using standard sieves with mesh sizes of 45 μm and 150 μm to obtain primary particles with a particle size of 45 μm to 150 μm.

[0118] (b) Reverse suspension polymerization. In this step, 124.4 g of acrylic acid was added to a 500 ml conical flask, and 189.9 g of a 27% by mass sodium hydroxide aqueous solution was added dropwise under an ice-water bath to neutralize 74% by mole of the acrylic acid, and then 0.192 g of potassium persulfate and 13.9 mg of N,N'-methylenebisacrylamide (No. 14085E, purchased from Adamas Reagent Co., Ltd.) were added and dissolved, and then 20 g of water was added to prepare the monomer aqueous solution of step 2.

[0119] Prepare a 1000mL detachable five-necked flask, install a reflux condenser, a nitrogen inlet tube, and a stirring paddle (crescent paddle with a blade diameter of 80mm) as a stirrer on the flask. Place the entire flask in an oil bath and heat it to 80°C, add 408ml of n-heptane, 1.104g of sucrose stearate (Mitsubishi Chemical Corporation, Ryoto sucrose ester S-370), and 1.104g of maleic anhydride modified ethylene-propylene copolymer (Mitsui Chemicals, Inc., Hi-wax1105A) to the flask, and wait for the dispersion stabilizer to dissolve. Adjust the speed to 500rpm, weigh 110g of the primary particles obtained by the aqueous solution polymerization in the above step and add them to the flask, and add 100g of water thereto.

[0120] The water bath temperature was lowered to 20°C, and the monomer aqueous solution of step 2 was added into the detachable flask. After the addition was completed, nitrogen was immediately used to replace the air in the system for 30 minutes. The flask was then immersed in a 70°C water bath for 60 minutes to obtain the slurry of step 2.

[0121] (c) Surface modification step: The slurry of step 2 is placed in an oil bath at 120°C to make water and n-heptane azeotropic. While ensuring the reflux of n-heptane, 230g of water is removed from the system, and then the oil bath temperature is cooled to 80°C. 10.34g of a 2% aqueous solution of ethylene glycol diglycidyl ether (No.: B38399B, purchased from Adamas Reagent Co., Ltd.) is added thereto, and kept at 80°C for 120min. Then the n-heptane is evaporated for drying, and 244.1g of secondary particles are obtained by the method. The median particle size of the secondary particles is 415.7μm, and the particle size distribution results are shown in Table 1. 100 parts by weight of the absorbent resin is mixed with 0.3 parts by weight of AEROSIL 200 (gas phase SiO2, Degussa) to obtain a final resin sample. The results of the performance measurements are shown in Table 2. Its SEM image shows that the product includes secondary particles formed by agglomeration of a large number of irregularly shaped primary particles.

[0122] Comparative Example 1

[0123] In this comparative example 1, a polymerization reaction design different from that of the method of the present invention is adopted, and both polymerization steps are reverse phase polymerization using hydrocarbon solvents, and the median particle size and performance of the final polymerization product are characterized. Specifically, the following steps are adopted in this comparative example:

[0124] Step 1 (polymerization reaction in a non-polar hydrocarbon solvent): 88.88 g of acrylic acid was added to a 500 ml conical flask, and 164.5 g of a 22% by mass sodium hydroxide aqueous solution was added dropwise thereto under an ice-water bath to neutralize 74% mol of the acrylic acid. Then, 0.132 g of potassium persulfate and 8.9 mg of N,N'-methylenebisacrylamide (No. 14085E, purchased from Adamas Reagent Co., Ltd.) were added to the flask and dissolved, and 20 g of water was added to the flask to prepare the first stage monomer aqueous solution.

[0125] Prepare a 1000mL detachable five-necked flask, install a reflux condenser, a nitrogen inlet tube, and a stirring paddle (crescent paddle with a blade diameter of 80mm) as a stirrer on the flask. Place the entire flask in an oil bath and heat it to 80°C, add 408ml of n-heptane to the flask, start the stirrer, adjust the stirring speed to 400rpm, add 1.104g of sucrose stearate and 1.104g of maleic anhydride modified ethylene-propylene copolymer (model: Hi-wax1105A, purchased from Mitsui Chemicals, Inc.) to the flask, and wait for the dispersion stabilizer to dissolve. Lower the oil bath temperature to 50°C, add the first-stage monomer aqueous solution prepared as described above to the above-mentioned detachable flask, immediately replace the air in the system with nitrogen, and after the addition is completed, immerse the flask in a 70°C oil bath and heat it to carry out a polymerization reaction. The polymerization time is 60min, and the first-stage slurry is obtained by polymerization. After the reaction was completed, the oil bath was cooled to 20°C.

[0126] Step 2: Prepare another 500 ml conical flask, add 124.4 g of acrylic acid to the flask, add 189.9 g of a 27% by mass sodium hydroxide aqueous solution dropwise thereto under an ice-water bath to neutralize 74 mol % of the acrylic acid, then add 0.192 g of potassium persulfate and 13.9 mg of N,N'-methylenebisacrylamide (No.: 14085E, purchased from Adamas Reagent Co., Ltd.) to the flask and dissolve them, then add 20 g of water to prepare the second stage monomer aqueous solution.

[0127] The second-stage monomer aqueous solution is added to the above-mentioned detachable flask containing the first-stage slurry, and the air in the system is replaced with nitrogen. After the addition is completed, the reaction flask is immersed in a 70°C oil bath to heat up and carry out the second-stage polymerization. The polymerization time is 60 minutes, and the second-stage slurry is obtained by polymerization.

[0128] Step 3 (modification step): The polymerized slurry obtained in step 2 is placed in an oil bath at 120°C to make water and n-heptane azeotropic. After removing 300g of water from the system while ensuring the reflux of n-heptane, the oil bath temperature is cooled to 80°C, and 10.34g of a 2% aqueous solution of ethylene glycol diglycidyl ether (No.: B38399B, purchased from Adamas Reagent Co., Ltd.) is added to the flask and kept at 80°C for 120min. Then the n-heptane is evaporated for drying, and 180.4g of secondary particles are obtained by the method. The median particle size of the secondary particles is 384.2μm, and the particle size distribution results are shown in Table 1. 100 parts by weight of the absorbent resin is mixed with 0.3 parts by weight of AEROSIL 200 (gas phase SiO2, Degussa) to obtain a final resin sample. The results of the performance measurements are shown in Table 2.

[0129] Comparative Example 2

[0130] In this comparative example 2, a polymerization reaction design different from that of the method of the present invention is adopted, and only aqueous solution polymerization is used to prepare the polymerization reaction product, and surface modification is performed after the polymerization reaction, and the median particle size and performance of the polymerization product are characterized. Specifically, the following steps are adopted in this comparative example:

[0131] In a PP beaker with a volume of 2000ml, 174.78g of acrylic acid (purchased from Shanghai Huayi New Materials Co., Ltd.), 148.19g of deionized water and 69.85g of a 50wt% NaOH aqueous solution (Shanghai Chlor-Alkali Chemical Co., Ltd.) were added. The NaOH solution needed to be added under strong stirring. During the addition of the NaOH solution, it was observed that a precipitate was formed, but the precipitate gradually dissolved to form a transparent uniform solution, and the temperature rose to 65°C. The material in the beaker was cooled to 56°C, and then 23.59g of a 4% aqueous solution of polyethylene glycol diacrylate 400 (Taiwan Changxing Materials Co., Ltd.) was added to the beaker as an internal crosslinking agent. Then 71.79g of a 50wt% NaOH aqueous solution at 40°C was added thereto. After the addition was completed, it was observed that the temperature of the material in the beaker rose to 88°C due to the neutralization heat. The temperature of the reaction liquid in the beaker was lowered to 78°C, and then 11.32g of a 3% sodium persulfate aqueous solution was added thereto to prepare the first-stage monomer aqueous solution. The monomer aqueous solution was stirred for 2 seconds, and then quickly stirred and poured into a 25*25cm stainless steel tray preheated to 105°C. The entire tray was placed in an oven at 105°C, and the polymerization reaction began after 20 to 30 seconds. During the polymerization reaction, water vapor was generated while expanding and bubbling in all directions, and then shrunk and collapsed into a size slightly larger than the polymerization disk. After 3 minutes from the start of the polymerization reaction, the ribbon-shaped hydrogel-like cross-linked polymer was taken out from the polymerization disk. The peak temperature during polymerization was 110°C.

[0132] The hydrogel obtained by the above polymerization reaction was broken up using a meat grinder (Zhengyuan Precision Machinery Co., Ltd., model RY-12S, pore size 8 mm) to obtain a granular hydrogel. During the gel breaking process, about 90 g of deionized water at a temperature of 90° C. was continuously sprayed onto the gel.

[0133] The granular hydrogel obtained by the above operation was spread on a stainless steel wire mesh with a mesh size of 850 μm and dried in a blast oven at 185° C. for 70 min. The dried polymer obtained by the drying operation was then crushed using a grinder and sieved and classified using standard sieves with mesh sizes of 150 μm and 600 μm to obtain particles with a particle size of 150 μm to 600 μm.

[0134] 0.6 parts by weight of methanol, 0.06 parts by weight of ethylene glycol diglycidyl ether and 4 parts by weight of deionized water are mixed to obtain a surface crosslinking solution. 100g of the absorbent resin particles obtained above are put into a stirring tank, and the stirring speed is set to 500rpm. Subsequently, 4.67g of the surface crosslinking solution is sprayed into the mixer to mix, thereby obtaining a coated wet material. Subsequently, the coated wet material is spread on a tray, placed in an 80°C oven, and the heating treatment time is 60min, thereby performing surface crosslinking to obtain an absorbent resin. 100 parts by weight of the absorbent resin are mixed with 0.3 parts by weight of AEROSIL 200 (gas phase SiO2, Degussa) to obtain a final resin sample. The median particle size of the particles obtained by the method is 351.7μm, and the particle size distribution results are shown in Table 1. The results of the performance measurements are shown in Table 2.

[0135] Comparative Example 3

[0136] In this comparative example 3, a polymerization reaction design different from that of the method of the present invention is adopted, and only aqueous solution polymerization is used to prepare the polymerization product, and surface modification is performed after the polymerization reaction, and the median particle size and performance of the polymerization product are characterized. Specifically, the following steps are adopted in this comparative example:

[0137] 154.8g of acrylic acid, 0.62g of crosslinking agent pentaerythritol triallyl ether (No.: 01140358, purchased from Adamas Reagent Co., Ltd.) and 343g of deionized water were mixed and stirred, and the temperature of the mixture was maintained at 3°C. Nitrogen was introduced into the mixture to make the dissolved oxygen content in the mixture below 1ppm, and then 0.6g of 1% hydrogen peroxide aqueous solution, 1g of 2% ascorbic acid aqueous solution and 2.3g of 2% 2,2-azobis[2-(imidazoline-2-yl)propane] dihydrochloride aqueous solution were added thereto while continuing to mix, and polymerization began. After the temperature of the mixture reached 90°C, the polymerization was continued at a temperature of 90±2°C for about 5 hours to obtain a hydrogel. Next, the hydrogel was ground with a meat grinder (Zhengyuan Precision Machinery Co., Ltd., model RY-12S, pore size 8mm), and 108g of 48.5% sodium hydroxide aqueous solution was added to neutralize it, 238773

[0138] A neutralized gel was obtained.

[0139] The granular hydrogel obtained by the above operation was spread on a stainless steel wire mesh with a mesh size of 850 μm and dried in a blast oven at 185° C. for 70 min. Next, the dried polymer obtained by the drying operation was crushed using a grinder and sieved and classified using standard sieves with mesh sizes of 150 μm and 600 μm to obtain primary particles with a particle size of 150 μm to 600 μm.

[0140] 0.6 parts by weight of methanol, 0.06 parts by weight of ethylene glycol diglycidyl ether and 4 parts by weight of deionized water are mixed to obtain a surface crosslinking solution. 100g of the absorbent resin particles obtained above are put into a stirring tank, and the stirring speed is set to 500rpm. Subsequently, 4.67g of the surface crosslinking solution is sprayed into the mixer to mix, thereby obtaining a coated wet material. Subsequently, the coated wet material is spread on a tray, placed in an 80°C oven, and heated for 60 minutes, thereby performing surface crosslinking to obtain an absorbent resin. The median particle size of the particles obtained by the method is 368.9μm, and the particle size distribution results are shown in Table 1. 100 parts by weight of the absorbent resin are mixed with 0.3 parts by weight of AEROSIL 200 (gas phase SiO2, Degussa) to obtain a final resin sample. The results of the performance measurements are shown in Table 2.

[0141] Comparative Example 4

[0142] In this Comparative Example 4, a polymerization reaction design different from that of the method of the present invention was adopted, and surface modification was performed between the aqueous phase polymerization step and the reversed phase suspension polymerization step and after the reversed phase suspension polymerization reaction.

[0143] (a) Aqueous phase polymerization step: In a PP beaker with a volume of 2000 ml, 174.78 g of acrylic acid (purchased from Shanghai Huayi New Materials Co., Ltd.), 148.19 g of deionized water and 69.84 g of a 50 wt% NaOH aqueous solution (purchased from Shanghai Chlor-Alkali Chemical Co., Ltd.) were added, wherein the NaOH solution needed to be added under strong stirring. During the addition of the NaOH solution, precipitates could be observed, but gradually dissolved to form a transparent uniform solution, and the temperature of the material rose to 65°C. The material was cooled to 56°C, and then 23.59 g of polyethylene glycol diacrylate 400 (purchased from Taiwan Changxing Materials Co., Ltd., as a 4% aqueous solution) was added as an internal crosslinking agent. Then 71.79 g of a 50 wt% NaOH aqueous solution at 40°C was added. After the addition was completed, the material temperature rose to 88°C due to the neutralization heat. The temperature of the reaction liquid was lowered to 78°C, and 11.32 g of a 3% sodium persulfate aqueous solution was added thereto to obtain the monomer aqueous solution of step one, which was stirred for 2 seconds. Then, while stirring, it was quickly poured into a 25*25 cm stainless steel tray preheated to 105°C, and the entire tray was placed in an oven at 105°C. After 20 to 30 seconds, the polymerization reaction began. During the polymerization reaction, water vapor was generated while expanding and bubbling in all directions, and then it shrank and collapsed into a size slightly larger than the polymerization disk. After 3 minutes from the start of the polymerization reaction, the cross-linked polymer containing a ribbon-like hydrogel was taken out from the polymerization disk. The peak temperature during polymerization was 110°C.

[0144] The hydrogel obtained by the aqueous phase polymerization reaction was broken up using a meat grinder (purchased from Zhengyuan Precision Machinery Co., Ltd., model RY-12S, pore size 8 mm) to obtain a granular hydrogel. During the gel breaking process, about 90 g of deionized water at a temperature of 90° C. was continuously and evenly sprayed onto the gel.

[0145] The granular hydrogel obtained by the above operation was spread on a stainless steel wire mesh with a mesh size of 850 μm and dried in a blast oven at 185° C. for 70 min. Next, the dried polymer obtained by the drying operation was crushed using a grinder and sieved and classified using standard sieves with mesh sizes of 45 μm and 150 μm to obtain primary particles with a particle size of 45 μm to 150 μm.

[0146] (b) Surface modification step:

[0147] Prepare five 1000mL detachable flasks, install a reflux condenser, a nitrogen inlet tube, and a stirring paddle (crescent paddle with a blade diameter of 80mm) as a stirrer on the flask. Add 408mL of n-heptane, 1.104g of sucrose stearate (Mitsubishi Chemical Corporation, Ryoto sucrose ester S-370), and 1.104g of maleic anhydride modified ethylene-propylene copolymer (Mitsui Chemicals, Hi-wax1105A) to the flask. Immerse the flask in a water bath, heat it to 80°C, wait for the dispersion stabilizer to dissolve, add 110g of primary particles after the solution is clarified, set the stirring speed to 400rpm, disperse the particles, add 32.49g of water, and continue to disperse for 15 minutes. 4.36 g of 2% aqueous solution of ethylene glycol diglycidyl ether (No. 38399B, purchased from Adamas Reagent Co., Ltd.) was added, and the temperature was maintained for 120 min. After the reaction was completed, 63.24 g of water was added. The primary particles obtained by this method completed the surface cross-linking reaction.

[0148] (c) Reverse suspension polymerization step: 124.4 g of acrylic acid was added to a 500 ml conical flask, and 189.9 g of a 27% by mass sodium hydroxide aqueous solution was added dropwise in an ice-water bath to neutralize 74 mol% of the acrylic acid. Then, 0.192 g of potassium persulfate and 13.9 mg of N,N'-methylenebisacrylamide (No. 14085E, purchased from Adamas Reagent Co., Ltd.) were added and dissolved, and 20 g of water was added to prepare the monomer aqueous solution of step (c).

[0149] The water bath temperature of the mixture obtained in step (b) was lowered to 20°C, and the monomer aqueous solution of step (c) described above was added to the flask. After the addition was completed, the air in the system was replaced with nitrogen for 30 minutes, and then the flask was immersed in a 70°C water bath for 60 minutes.

[0150] (d) Surface modification step: The polymerized slurry obtained in step (c) was placed in an oil bath at 120°C to make water and n-heptane azeotropic. While ensuring the reflux of n-heptane, 300 g of water was removed from the system, and the oil bath temperature was lowered to 80°C. 10.34 g of a 2% aqueous solution of ethylene glycol diglycidyl ether (No. B38399B, purchased from Adamas Reagent Co., Ltd.) was added to the flask and kept at 80°C for 120 min. Then, the n-heptane was evaporated for drying. 260.4 g of secondary particles were obtained by the method. The median particle size of the secondary particles was 382.3 μm, and the particle size distribution results are shown in Table 1. 100 parts by weight of the absorbent resin was mixed with 0.3 parts by weight of AEROSIL 200 (gas phase SiO2, Degussa) to obtain a final resin sample. The results of the performance measurements are shown in Table 2.

[0151] The particle size distribution of the water-absorbent resin obtained in the above-mentioned embodiments and comparative embodiments is shown in Table 1, and the performance is shown in Table 2.

[0152] Table 1

[0153]

[0154] Table 2

[0155]

[0156] The SAP particles prepared by the method of the present invention are formed by agglomeration of irregularly shaped small particles, which are primary particles obtained by polymerization, crushing and classification in the first stage. In the second stage polymerization, the molecular chains formed by the polymerization of the newly added second polymerization monomer link these primary particles to form a Figure 1A and 1B The final secondary particle morphology is shown. From the comparison between the examples and the comparative examples, it can be seen that the method of the present invention can significantly improve both the liquid permeability and the salt water absorption rate of the product.

Claims

1. A method for preparing a water-absorbent resin, the method comprising the following steps: Step 1: allowing the first polymerizable monomer to undergo a first polymerization reaction in an aqueous solution phase to obtain a prepolymer; Step 2: forming a dispersion of the prepolymer in a non-polar solvent, adding a second polymerizable monomer into the dispersion, and performing a second polymerization reaction to obtain an intermediate resin; Step 3: modifying the intermediate resin with a surface cross-linking agent to obtain the water-absorbent resin; and The first polymerized monomer and the second polymerized monomer are compounds containing at least one carbon-carbon double bond and at least one active group, respectively. The first polymerized monomer and the second polymerized monomer are the same or different.

2. The method according to claim 1, characterized in that Before performing step three, no surface modification was performed using a surface cross-linking agent.

3. The method according to claim 1, characterized in that The surface crosslinking agent is a polyol poly(glycidyl ether).

4. The method according to claim 1, characterized in that In step 1 and / or step 2, one or more internal crosslinking agents are optionally used, and the internal crosslinking agents are selected from one or more of the following: poly(unsaturated carboxylic acid) polyol esters, polyacrylamides, poly(meth)acrylic acid carbamoyl esters, allylated starch, allylated cellulose, polycarboxylic acid poly(allyl esters), polyallyl isocyanurate, polyvinyl aromatic compounds, polyol poly(allyl) ethers.

5. The method according to claim 1, characterized in that The first polymerizable monomer and the second polymerizable monomer are the same as or different from each other, and are independently selected from one or more of the following: (meth)acrylic acid, C1-C12 alkyl (meth)acrylate, C1-C12 hydroxyalkyl (meth)acrylate, (meth)acryloyl C2-C12 alkyl sulfonate, (meth)acrylamide C2-C12 alkyl sulfonic acid, hydroxyalkyl (meth)acryloyl phosphate, itaconic acid, cinnamic acid, vinyl sulfonic acid, allyl toluene sulfonic acid, vinyl toluene sulfonic acid, styrene sulfonic acid, (meth)acrylamide, N-ethyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylamide, mercapto-containing unsaturated monomers, phenolic hydroxyl-containing unsaturated monomers, and N-vinyl pyrrolidone; The molar ratio of the first polymerized monomer to the second polymerized monomer is 1:10 to 10:

1.

6. The method according to claim 1, characterized in that After step one and before step two, the prepolymer prepared in step one is crushed and sieved to obtain first primary particles of prepolymer with a median particle size of greater than or equal to 10 microns and less than 150 microns, which are used in step two.

7. The method according to claim 1, characterized in that In the step 1 and the step 2, one or more selected from the following are optionally used: an initiator, a dispersion stabilizer, and an alkaline agent; In the step 2, the non-polar solvent is selected from one or more of the following: n-hexane, n-heptane, cyclohexane, toluene and xylene; Optionally, an inorganic additive is added during, before or after one or more of steps 1 to 3.

8. The method according to claim 1, characterized in that The water-absorbent resin is in the form of secondary particles formed by agglomeration of second primary particles, the median particle size of the secondary particles is 250-500 microns, and the median particle size of the second primary particles is 15-150 microns.

9. The method according to claim 1, characterized in that The step 1 is carried out at a temperature of 45-120° C., so that 60-100% of the first polymerizable monomer is polymerized; The step 2 is carried out at a temperature of 60-95°C; The step three is carried out at a temperature of 50-100° C., and based on the total weight of the second polymerizable monomer being 100 weight %, the amount of the surface crosslinking agent is 0.001-1 weight %.

10. A water-absorbent product, comprising: Diapers, sanitary napkins, adult care pads, absorbent paper, napkins, disposable mattresses, soil moisturizing materials, leak-proof materials, water-blocking materials, sewage treatment materials, and mud solidification materials; At least a part of the water-absorbent product comprises a water-absorbent resin prepared by the method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for producing water-absorbent resin particles, and water-absorbent resin particles

    CN114787244A

  • Method for producing water-absorbent resin

    CN116375944A

  • Process for production of water-absorbable resin particle, and water-absorbable resin particle produced by the process

    US20090281247A1